Clinical assessment to identify pelvic injuries in the prehospital setting: a prospective cohort study - Coulombe, Pascale; Robitaille-Fortin, Maxime; Nadeau, Alexandra; Malo, Christian; Blanchard, Pierre-Gilles; Benhamed, Axel; Émond, Marcel; Mercier, Eric (Frontiers in Disaster and Emergency Medicine, 2024)
This study aimed to assess how pelvic examination is performed by paramedics and to determine the accuracy of their clinical examination to identify pelvic fractures.This was a prospective cohort study of prehospital interventions including both real and simulated trauma patients. Data collection for injured patient was made by an observer who was paired with two consenting paramedics. Data pertaining to the clinical assessment for pelvic injuries during all interventions with a trauma patient was collected. Also, data was collected during four simulated scenarios of patients with an open-book type pelvic fracture following high-energy trauma mechanisms.A total of 29 trauma-related clinical interventions were assessed. Most patients were female (n=22, 75.9%) with a mean age of 69.8 (SD 22.2) years old. Fall from standing was the main trauma mechanism (n=21, 72.4%). During 72.4% (n=21) of all trauma-related interventions, an assessment for pelvic injuries was performed, mostly by pelvic palpation (n=19, 65.5%), inquiring about the presence of pain (n=12, 41.4%), searching for deformation (n=7, 24.1%) and/or assessing leg length (n=8, 27.6%). No pelvic injury was suspected by the paramedics, but 2 (6.9%) patients had a pelvic fracture and 2 (6.9%) had a hip fracture. Simulated cases of high-velocity mechanisms with an open-book pelvic fracture were completed by 11 pairs of paramedics. Most did a clinical pelvic assessment (n=8, 72.7%) using palpation. When asked after the simulation, 9 pairs (81.8%) suspected a pelvic fracture. Pelvic injuries are challenging to identify, and pelvic assessment on the field is not standardized among paramedics.